To be born twin: effects on long-term neurodevelopment of very preterm infants—a cohort study - Fontana, Camilla; Schiavolin, Paola; Ardemani, Giulia; Amerotti, Danila Angela; Pesenti, Nicola; Bonfanti, Chiara; Boggini, Tiziana; Gangi, Silvana; Porro, Matteo; Squarza, Chiara; Giannì, Maria Lorella; Persico, Nicola; et al. (Frontiers in Pediatrics, 2023)
Objective To examine the effect of twin birth on long-term neurodevelopmental outcomes in a cohort of Italian preterm infants with very low birth weight. Study design We performed a retrospective cohort study on children born in a tertiary care centre. We included children born between 1 January 2007 and 31 December 2013 with a gestational age (GA) of ≤32 weeks and birth weight of <1,500 g. The infants born from twin pregnancies complicated by twin-to-twin transfusion syndrome and from higher-order multiple pregnancies were excluded. The children were evaluated both at 2 years corrected age and 5 years chronological age with Griffiths mental development scales revised (GMDS-R). The linear mixed effects models were used to study the effect of being a twin vs. being a singleton on GMDS-R scores, adjusting for GA, being born small for gestational age, sex, length of NICU stay, socio-economic status, and comorbidity score (CS) calculated as the sum of the weights associated with each of the major morbidities of the infants. Results A total of 301 children were included in the study, of which 189 (62.8%) were singletons and 112 (37.2%) were twins; 23 out of 112 twins were monochorionic (MC). No statistically significant differences were observed between twins and singletons in terms of mean general quotient and subscales at both 2 and 5 years. No effect of chorionicity was found when comparing scores of MC and dichorionic twins vs. singletons; however, after adjusting for the CS, the MC twins showed lower scores in the hearing and language and performance subscales at 5 years. Conclusion Overall, in our cohort of children born very preterm, twin infants were not at higher risk of neurodevelopmental impairment compared with singletons at pre-school age.